Surgeon factor on laser in situ keratomileusis in low and moderate myopia (Faculty of Medicine Universitas Indonesia, 2003)
The purpose of this study was to evaluate the effectiveness and predictability of laser in situ keratomileusis (LASIK) procedure performed by three surgeons in low and moderate myopia. One hundred twenty nine eyes from 68 patients underwent LASIK procedure, performed by three different surgeons (X, Y, Z) using the same procedure and same instruments were reviewed. These patients are divided into two groups, group A (below - 6.00 diopters) and group B (between - 6.00 and - 10.00 diopters). Patients were observed on day 1, day 7, 1st month and 3rd month. Results: The evaluation of effectiveness and predictability is based upon uncorrected visual acuity (UCVA) and spherical equivalent refraction, respectively. The variation dispersion between attempted correction and achieved correction is measured using coefficient of determination (R2). The statistical analysis shows indifferent results for the three surgeons. The conclusion was that the effectiveness and predictability of LASIK procedure performed by the three surgeons in both groups are indifferent. Hence, this study suggests that the surgeon factor does not affect the result of LASIK procedure. (Med J Indones 2003; 12: 148-54)